Nouvelles recherches flamandes. - Musée Rath, Genève (Genève : Musée Rath, 1965)
Van Anderlecht, Englebert ; Bogart, Bram ; De Leeuw, Bert ; Gentils, Vic ; Van Hoeydonck, Paul ; Leblanc, Walter ; Mees, Guy ; Raveel, Roger ; Vandenbranden, Guy ; Verheyen, Jef
Nouvelles recherches flamandes, Musée Rath, Genève, 27 mars - 2 mai 1965
boek